ISLAM DAN POSFEMINISME : Wajah Posfeminisme Dalam Komodikasi Agama di Media - M Ali Sofyan (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
The relationship between masculine and feminine is collectively constructed. Both narrative and discourse of feminism has long emerged up to the third-wave. As Foucault has been pointed out that feminism itself has constructed discourse on inequality since it departs from patriarchy. Meanwhile, patriarchy has produced a threat even though it is under the pretext of feminism. The term postfeminism is thus arises after feminism, where there are no sources of oppression that originate from patriarchy.In fact, however, the interpretation of religious arguments (Islam in particular) does not subordinate women. But on the contrary, the religious argument actually wants to make women equal to men in the society. This article offers an analysis of the relation between Islam and postfeminism based on the perspective of religious commodification. It was noted that social media played a pivotal role in raising religion to engage on a global scale.Women from the perspective of postfeminism are seen as independent subjects. Freedom, gender equality, and pluralistic representation are the starting points for postfeminist women. Soft Power owned by social media contextualizes religion (Islam) and disseminates ideas including femininity in a new method, where the religious consumption can be enjoyed every second.Indonesian (Muslim) women campaign for gender equality and postfeminism awareness that is free in all things through social media (Instagram and YouTube). This is usually done in various ways such as lectures and fashion. Religious commodification, in this case is seen when religious understanding is capitalized. This perspective finally bringing Muslim women to say that